RESILIENCE, RELIGIOUS ORIENTATION, AND EMOTION REGULATION AMONG FIRST-YEAR THEOLOGICAL STUDENTS - Sitepu, Elisabeth; Simamora, May Rauli; Hasugian, Johanes Waldes (International Journal of Research -GRANTHAALAYAH, 2021)
The purpose of this study was to determine the relationship between religious orientation, emotion regulation, and resilience of first-year theological students. The total sample used in this study was 59 first-year theological students at a theological college in Indonesia. The results show a statistically significant positive relationship between religious orientation, emotion regulation, and resilience. The results also show that the effective contribution of emotion regulation is higher than the religious orientation towards resilience. These results indicate the importance of emotional regulation training and religious orientation education to develop resilience in the lives of first-year theological students.